Lifestyles and habits of a Spanish University Community in times of COVID-19: a cross-sectional study (Estilos de vida y hábitos de una Comunidad Universitaria Española en tiempos de COVID-19: un estudio transversal) - Gustavo Rodriguez-Fuentes; Pablo Campo-Prieto; Jose María Cancela-Carral (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Background: COVID-19 pandemic caused unprecedented disruption in everyone´s worldwide. The lockdown and related restrictions to which the Spanish population was subjected affected the general health of our society as a whole. Objective: The aim of the study was to explore the impact of the COVID-19 pandemic on the lifestyle and habits of the University of Vigo community -Spain-. Method: A descriptive, observational, cross-sectional study was carried out by means of an anonymous 76-question survey. Results: 418 questionnaires were received, 359 (85.88%) were considered valid for the analysis. Population performed physical activity several times a week (59.39%), non-smokers (89.76%), occasional drinkers (>40% drink no more than 2-3 times/month), slept 7.06±0,9 hours/day and the 60.59% perceived their current state of health as good. During the lockdown they remained active (56.31%), followed safe recommendations (96.86%), had contact with infected people (42%), developed the disease (6%), and required hospital admission (0.40%). People surveyed about the pandemic situation were quite or very concerned (89.84%), had a negative quality life impact (75.20%), and suffered muscle and joint pain due to overuse of electronic devices (66.26%). Conclusion: Our findings show healthy lifestyle, balancing physical activity and/or sports routines with adequate rest and by minimising toxic habits. This behaviour maintained over time, together with following the safe recommendations, may have a protective role in the mental and physical health, minimizing the negative influence of COVID-19.